P0988THE PROTECTIVE EFFECT OF RED ORANGE AND LEMON EXTRACT (RLE) IN DIABETIC OBESE ZUCKER RATS IS RELATED TO ITS ACTION ON THE NADPH OXIDASE SUBUNIT. (6th June 2020) - Damiano, Sara; Longobardi, Consiglia; Lauritano, Chiara; Andretta, Emanuela; Capasso, Giovambattista; Florio, Salvatore; Ciarcia, Roberto
Abstract: Background and Aims: Type 2 diabetes mellitus is a pathological and chronical condition that induce a rearrangement in carbohydrate metabolism (Kaneto H et al. Antioxid Redox Signal. 2007). Even if the pathological mechanism of DN is not yet clear, NADPH oxidase (NOX) has been demonstrated to be involved in kidney ROS (Reactive Oxygen Species) generation during diabetic state (Palicz A. et al. J Biol Chem. 2001). Therefore, NOX-4, whose p22-phox subunit have shown a pivotal role in diabetes development, has been considered a potential pharmacological target in DN (Gill PS and Wilcox CS. Antioxid Redox Signal. 2006). In previous experiments performed on diabetic rat animal model with DN, we have found a beneficial effect of an extract rich in anthocyanins (ANT), members of flavonoids group (Shih PH. J Agric Food Chem. 2007). The aim of the present work was to investigate the molecular mechanisms involved in the DN and the protective effects of the new extract particularly abundant in ANT, the Red orange and Lemon Extract (RLE). Method: Zucker diabetic fatty rats were divided into three groups and treated by gavage daily until 30 weeks of age, as follows: control group (ZF rats) received 1 mL of normal saline; ZDF Group (ZDF rats) received 1mL of normal saline; ZDF + RLE group (ZDF rats) treated with 90 mg/ kg of RLE dissolved in 1mL of normal saline. We examined the gene and protein expression of NOX4 catalytic subunit and its regulatory subunit p22-phox through Real Time PCR and western blot analysis. Results: The expression gene levels of NOX4 significantly increased in diabetic rats ZDF, compared to control ZF (***p<0.001). Exposure of ZDF rats with RLE induces a decreased expression of NOX4 (Figure 1 ) compared to ZDF. On the contrary, there were not significant expression levels variations for regulatory subunit p22-phox. Western blot results are in agreement with Real Time PCR data, in fact an increase in NOX4 protein levels (*p<0.05) is evident, but no significant increase in p22-phox subunit was observed. Conclusion: In conclusion, we hypothesize that the protective effect of RLE on the development of DN is related to its ability to inhibit NADPH oxidase activity and opens new perspectives for the treatment of DN.